Suicide Ideation Among Healthcare Professionals - Sakinah Abdallah Almanasif; Fatimah Mohammad Al Yaseen; Sarah Ibrahim Mahdi Albadan3; Marwa Ibrahim Mahdi Al Badan; Heba Ibrahim Albadan; Raeeda Ibrahim Albadan; Amal Makki Hassan Al Marhoon; Yassmin Saud Abd Alaziz Alrebh; Fatima Saud Abdulaziz Alrebh; Narjes Hussain Ali Al Rubh; Haniah Mahadi Alakash; Layla Nasser Alhassan; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
Suicide ideation among healthcare professionals is a serious and complex issue that warrants attention. This review aims to explore the prevalence, risk factors, and preventive strategies related to suicide ideation among healthcare professionals.